EXPERIMENTAL STUDY OF FINE GRAIN CONTENT OF SOIL ON LIQUEFACTION POTENTIAL - Maulana Arif; Ilpandari Ilpandari (FROPIL (Forum Profesional Teknik Sipil), 2022)
One of the efforts to realize environmentally sound development is to pay attention to disaster aspects that threaten an area, one of which is the phenomenon of liquefaction. The liquefaction disaster is of particular concern after the 2018 Palu liquefaction, damaging and claiming many victims. Liquefaction is a phenomenon in soils that are initially solid and then turn liquid due to increased pore water pressure due to cyclic loads or earthquakes, which reduce the carrying capacity of the soil. Not all types of soil have the potential to experience liquefaction. In general, soils with a high liquefaction potential are soils with a high content of fine sand grains and fewer clay particles. This study aims to determine the effect of fine grain content (silt and clay) on the magnitude of the liquefaction potential. The study was conducted using experimental modeling with fine sand soil samples (passed sieve number 40 and retained sieve number 100), which varied the content of fine grains (passed sieve number 200) as much as 0%, 5%, 10%, 15%, and 20%. The results of this study indicated that soil with a fines content of 0% liquefied after 5.56 seconds, and soil with a fines content of 20% experienced liquefaction after 23.84 seconds. This condition shows that the higher fine content of soil decreases its liquefaction potential.